SUMMARY AND ANALYSIS OF MEAT SUBSTITUTES - Ozodbekova Azizakhon Pulatjon qizi (Modern American Journals, 2025)
This article analyses meat substitutes as a response to the environmental impact and health concerns associated with meat production. It looks at the different types of substitutes—plant-based, mycoprotein, and lab-grown meats—and discusses the ability of each type to reduce greenhouse gas emissions, conserve vital resources, and promote healthier diets.The discussion addresses important reasons why meat substitutes may or may not be accepted by consumers. These scientific perceptions, taste, nutrition, and cost. The article also discusses the technology and other social concerns that aim to develop safe protein alternatives. This research is important because it provides relevant information in relation to the growing concern of sustainability by integrating alternative meat research, market developments, and innovations into one coherent narrative.
Keywords: This article analyses meat substitutes as a response to the environmental impact and health concerns associated with meat production. It looks at the different types of substitutes—plant-based, mycoprotein, and lab-grown meats—and discusses the ability of each type to reduce greenhouse gas emissions, conserve vital resources, and promote healthier diets. The discussion addresses important reasons why meat substitutes may or may not be accepted by consumers. These scientific perceptions, taste, nutrition, and cost. The article also discusses the technology and other social concerns that aim to develop safe protein alternatives. This research is important because it provides relevant information in relation to the growing concern of sustainability by integrating alternative meat research, market developments, and innovations into one coherent narrative.